Design of a composite golf driver club head - Colin de Verdiere, Mathieu (Cranfield University, 2004)
The game of golf is enjoyed by a large number of people, from all over the world. According to the rules of golf, each player has to choose from a maximum of 14 clubs, before playing a shot. This makes the number of pieces of equipment required much higher than in any other ball related sport. This research project focuses on the design of a composite golf driver club head, the club head being the part of the golf club that strikes the ball. The driver club head is selected when a golfer wants to achieve a long distance shot. Modern driver heads are manufactured from metal, either steel or titanium and their performance can be defined as the accuracy and length of a shot. An investigation is made to compare the performance of composite and metal club heads. The project included a study of an existing composite golf driver and the design of a new driver. The new shape was analyzed using non linear finite element software (Ls Dyna), and some overall design in composites and metals were done. It was found that the front face structural properties and geometry were critical to club’s performances. So initially the front face only was considered (smaller model) using Ls Dyna and Nastran, before focusing again on the complete club head. Once the best design was done an attempt to manufacture a prototype was made in order to try to validate the computer model. Experiments revealed that the new driver shape had a higher moment of inertia, which improves the accuracy of a shot, than the existing Callaway C4 club, for the same mass. The ball speed after impact for the new driver was 0.2 m/s less, when using a high strength carbon epoxy composite material compared to a titanium one. For this reason, it is concluded that it is possible to achieve similar overall performances with composite and titanium heads. It is anticipated that with more research into stronger fibres, 3 D fabrics and nano-reinforcements, a carbon composite club head will offer a greater overall performance than metallic golf club heads.